2022
DOI: 10.1002/adma.202207786
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic‐Microgels‐Enabled Rapid Water Extraction from Arid Air

Abstract: Sorbent‐based atmospheric water harvesting (AWH) has emerged as a promising decentralized water‐production technology to mitigate the freshwater crisis in arid areas. Hydrogels have been regarded as attractive sorbents due to their high water retention and tailorable polymer–water interactions. Yet, the kinetics of water sorption and desorption at low relative humidity (RH) shall be improved for their practical implementation. Here, hygroscopic microgels (HMGs) composed of hydroxypropyl cellulose (HPC) and hyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…According to methods in the literature, we measured the water content ( Q ), water contact angles, water vapor adsorption and desorption curves, and water transport rate of the four COF gels (Figure c and Figures S83–S85). The water content and water transport rates of TpAzo, NKCOF-1, NKCOF-60, and NKCOF-61 hydrogels were 38.2, 37.4, 45.5, and 48.6 g/g and 15.2, 15.9, 22.9, and 29.3 g/min, respectively. From the results, the four COF gels have a high water content and water transfer rate, with the best performance of NKCOF-61.…”
Section: Results and Discussionmentioning
confidence: 99%
“…According to methods in the literature, we measured the water content ( Q ), water contact angles, water vapor adsorption and desorption curves, and water transport rate of the four COF gels (Figure c and Figures S83–S85). The water content and water transport rates of TpAzo, NKCOF-1, NKCOF-60, and NKCOF-61 hydrogels were 38.2, 37.4, 45.5, and 48.6 g/g and 15.2, 15.9, 22.9, and 29.3 g/min, respectively. From the results, the four COF gels have a high water content and water transfer rate, with the best performance of NKCOF-61.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[95] Another solution to address the energy-intensive regeneration process is developing hydrogels with thermoresponsive polymers via molecular engineering to facilitate water release. [96] Thermoresponsive hydrogels such as PNIPAm, poly (N-vinyl caprolactam) (PVCL), and hydroxypropyl cellulose (HPC) [85,97] act as water molecule reservoirs in low temperatures and store the sorbed water in their hydrophilic structure. With a small temperature variation, they transform to their hydrophobic structure and release the stored water in liquid state with minimal energy consumption.…”
Section: Novel Synthetic Materialsmentioning
confidence: 99%
“…[84] Hydrogels can sorb a considerable amount of liquid water; however, their porosity and kinetics may require further enhancement to boost the sorption of moisture from the air. [85] In the sorption kinetics of hygroscopic hydrogels, vapor transport in the hydrogel micropores and liquid transport in the polymer nanopores are two chief coupled processes. Liquid transport caused by the gradient of chemical potential in the hydrogel is a significant factor in the fast kinetics.…”
Section: Novel Synthetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In recent years, there has been more and more research on various atmospheric water harvesting materials based on adsorbents. Guan et al 5 reported hygroscopic microgels composed of hydroxypropyl cellulose (HPC) and hygroscopic salts. Aleid et al 1 discovered that the salting-in effect of a zwitterionic hydrogel can facilitate water vapor sorption by the hygroscopic salt under otherwise identical conditions.…”
Section: Introductionmentioning
confidence: 99%